Penerapan Good Logistic Practices Sebagai Penunjang Ekspor Buah Tropis - Winiati Pudji Rahayu; Wibisono Adhi (Institut Transportasi dan Logistik Trisakti, 2015)
One strategy that can be taken to develop the economic potential of fruits is the logistical support that takes into account the effectiveness and efficiency commercially and pay attention to quality and food safety requirements. Practically, logistics support can be done with the application of good logistics practices (GLP). Packaging, storage, and handling during transportation become key activities with temperature and time handling during processing as two critical factors in fruits logistics management that will determine the final quality of fruits commodity. Each commodity of tropical fruits require special treatment which should be tailored to its nature and morphology. Understanding and the ability of farmers and agro-industry entrepreneurs in dealing with fruits especially in providing cold chain in the logistics process becomes a major capital to compete with imported fruits entrepreneurs.